Perlindungan Hukum Terhadap Tenaga Kerja Wanita Harian Lepas: Studi Kasus PT. Rinjani Tirta Abadi Di Desa Aik Berik - Renda Hizanatul Ulumi; Any Suryani Hamzah (Fakultas Hukum Universitas Mataram, 2022)
This study aims to determine the legal protection of daily female laborers at PT. Rinjani Tirta Abadi in Aik Berik Village in terms of Law Number 13 of 2003 concerning Manpower. A female worker is a woman who works for wages or other forms of remuneration. Daily laborers are workers or laborers who work for entrepreneurs to carry out certain jobs that can vary in terms of time and volume of work by receiving wages based on the daily attendance of workers. The type of research used in this study is empirical legal research with a sociological juridical approach and uses primary legal sources obtained from field data and interviews. Law Number 13 of 2003 concerning Manpower has provided regulations regarding the rights of women workers. Based on the formulation of the problem and the purpose of this study, namely, to analyze further how the legal protection arrangements for daily workers at PT. Rinjani Tirta Abadi, and to find out the implementation of protection for daily female workers based on Law No. 13 of 2003 concerning Manpower.